FREQUENCY OF HUMAN LEUCOCYTE ANTIGEN (HLA) CLASS I (A,B,C) DIVERSITY COUPLED WITH IMMUNOMOLECULAR PANEL: A POTENTIAL IMMUNOGENETIC MARKER FOR HEPATITIS B INFECTION - Shrestha, Smita; Das Manandhar, Krishna (Journal of Chitwan Medical College, 2024)
Background: Hepatitis B virus infection involves a complex interplay of the host pathogen interaction. The host factors involves the Human Leucocyte Antigen molecule, associated with the persistence or clearance of the infection in a population. Viral factors involves antigen, antibody and viral copy number. The aim of the study was to generate a combined information on the serology panel, copy number and HLA diversity as immunogenetic markers in an HBV infected population. Methods: This quantitative study was conducted at the Central department of Biotechnology, Tribhuvan university , Sukraraj Tropical Hospital and National Public Health Laboratory ,Teku in the time period of December 2018 to march 2020. Serological panel was detected followed by the copy number of the virus. Diversity of class I HLA –A, B and C was detected by sequencing. Calculation were performed by SPSSv.22 and graphically represented by PrismPad.v.5. Results: Out of the total 828 Hepatitis B positive patients, majority of 56.15% detetcted the serological panel of HBsAg+/HBeAg-/ HBsAb-/HBeAb-/HBcAb±/IgMHBcAb± . The highest detection of copy numbers in the range of 20-20,000 IU/ml(70.14%). Diversity detected was HLA A*11:01, A*68:01, B*15:01, B*15:05, B 15:18, B*15:25, B*15:32, C*04:01, C*04:03 in Hepatitis B infected individuals as compared to the healthy controls. The level of significance was detected in the HLA A*11:01(p=0.02) and A*68:01(p=0.01) in HBV infected individuals. Conclusions: Serological panel, copy number and HLA detects immunogenetic markers in Hepatitis B infected patients which can aid in better management and treatment of the infection.